Lost in Translation: What do Engel Curves Tell us about the Cost of Living? - Ingvild Almås; Timothy K.M. Beatty; Thomas F. Crossley (Center for Economic Studies and ifo Institute (CESifo), 2018)
The Hamilton method for estimating CPI bias is simple, intuitive, and has been widely adopted. We show that the method confiates CPI bias with variation in cost-of-living across income levels. Assuming a single price index across the income distribution is inconsistent with the downward sloping Engel curves that are necessary to implement the method. We develop and implement the Translated Engel curve (TEC) method that disentangles genuine CPI bias from differences caused by comparing changes in the cost of living across different income levels - non-homotheticity. The TEC method gives substantially different estimates of CPI bias prior to major reforms to the CPI in 1999 (post-Boskin), but both methods suggest very little CPI bias thereafter.
Keywords: C43; C82; D12; D31; E31; 330; Engel curves; current price index; cost of living